Linear and Annular Lupus Panniculitis of the Scalp with Annular Lupus Panniculitis of the Face in a Child - Narayanan Baskaran; Prashant Bharti; Sudheer Arava; Sujay Khandpur (Indian Dermatology Online Journal, 2024)
Linear and annular lupus panniculitis of the scalp is a rare form of lupus panniculitis recently reported in literature. It presents as linear or annular or arciform areas of nonscarring alopecia of the scalp with minimal surface changes. We report a 4-year-old Indian female child with arciform erythematous plaque over the forehead extending on the scalp with nonscarring alopecia with annular erythematous plaque over the cheek. Histology showed lobular lymphocytic panniculitis with abundant mucin deposition. Antinuclear antibody and systemic screen for lupus were negative. After treatment with oral corticosteroids, complete remission was achieved with good regrowth of scalp hair with no relapse during the follow-up period of 6 months. This is the youngest reported case of linear and annular lupus panniculitis of the scalp.